2017
DOI: 10.1177/1756283x17702614
|View full text |Cite
|
Sign up to set email alerts
|

Is EUS-guided drainage a suitable alternative technique in case of proximal biliary obstruction?

Abstract: Background:Results of endoscopic ultrasound-guided biliary drainage (EUBD) are unknown in case of proximal stricture. The aim is to assess clinical outcomes of EUBD in patients with malignant hilar obstruction.Methods:Patients undergoing EUBD with hilar strictures were prospectively included. Primary outcome was clinical success at 7 and 30 days (defined by 50% bilirubin decrease). Secondary outcomes were technical success, procedure-related complications, length of hospital stay, reintervention rate, survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 16 publications
1
37
0
3
Order By: Relevance
“…A study done by Moryoussef et al . also showed results of EUS‐BD in patients with MHBO . Eighteen patients were included with 15 classifiable stenosis only: seven (47%) were noted as Bismuth I–II, seven (47%) as Bismuth III, and one (6.7%) as Bismuth IV.…”
Section: Results Of Previous Studies For Eus‐bd In Mhbomentioning
confidence: 99%
See 1 more Smart Citation
“…A study done by Moryoussef et al . also showed results of EUS‐BD in patients with MHBO . Eighteen patients were included with 15 classifiable stenosis only: seven (47%) were noted as Bismuth I–II, seven (47%) as Bismuth III, and one (6.7%) as Bismuth IV.…”
Section: Results Of Previous Studies For Eus‐bd In Mhbomentioning
confidence: 99%
“…A study done by Moryoussef et al also showed results of EUS-BD in patients with MHBO. 8 Eighteen patients were included with 15 classifiable stenosis only: seven (47%) were noted as Bismuth I-II, seven (47%) as Bismuth III, and one (6.7%) as Bismuth IV. Reasons for EUS-BD were surgically modified anatomy in 10 patients (55.6%), impassable stricture at ERCP in seven (38.9%) and duodenal obstruction in one (5.6%).…”
Section: Results Of Previous Studies For Eus-bd In Mhbomentioning
confidence: 99%
“…published a first case series with seven patients describing this bridge technique,[7] which was already described in an abstract by our team. [15] More recently, a French team described this kind of drainage being used in three patients[8] in a series of 18 patients with hilar strictures and failure of ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Moryoussef et al . [8] tried to answer the question regarding the technical success rate, finding a success rate of 50%, but with only three patients. Case description was limited because of this retrospective design, especially if the pejorative evolution of Type III (salvage PCT) and IV (death on day 7) is due to nondrainage of the opacified segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation